(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
Starting from the System Justification Theory, the aim of this paper is to explore levels of general system legitimation, inequality perception and meritocracy perception among Croatian citizens, as well as to determine whether there is a difference between social groups of lower and higher social standing in this regard. Survey research on a sample of the Croatian general population (N = 353) revealed that on balance the respondents do not perceive the Croatian social system as legitimate, equal and meritocratic. Regression analyses showed that retired persons express a substantially higher level of system legitimation and meritocracy perception when compared to employed persons, while higher religiosity was also a significant predictor in this regard. When it comes to the inequality perception, only female gender was a significant predictor. The results are discussed within the framework of the contemporary theories of meritocracy and system legitimation, as well as with reference to specific social and economic characteristics of the Croatian society, such as the Croatian War of Independence, transition to capitalism, welfare state development and labour market situation. Overall, the study results provide only a partial confirmation of the System Justification Theory.